Observation and enhancement of room temperature bilinear magnetoelectric resistance in sputtered topological semimetal Pt3Sn - Yihong Fan; Zach Cresswell; Yifei Yang; Wei Jiang; Yang Lv; Thomas J. Peterson; Delin Zhang; Jinming Liu; Tony Low; Jian-Ping Wang (npj Spintronics)
Abstract Topological semimetal materials have attracted a great deal of attention due to their intrinsic strong spin-orbit coupling, which leads to large charge-to-spin conversion efficiency and novel spin transport behaviors. In this work, we have observed a bilinear magnetoelectric resistance (BMER) of up to 0.0034 nm2A−1Oe−1 in a single layer of sputtered semimetal Pt3Sn at room temperature. Being different from previous works, the value of BMER in sputtered Pt3Sn does not change out-of-plane due to the polycrystalline nature of the Pt3Sn layer. The observation of BMER provides strong evidence of the existence of spin-momentum locking in the sputtered polycrystalline Pt3Sn. By adding an adjacent CoFeB magnetic layer, the BMER value of this bilayer system is doubled compared to the single Pt3Sn layer. This work broadens the material system in BMER study, which paves the way for the characterization of topological states and applications for spin memory and logic devices.